1995
DOI: 10.1006/viro.1995.1016
|View full text |Cite
|
Sign up to set email alerts
|

Vpr Is Required for Efficient Replication of Human Immunodeficiency Virus Type-1 in Mononuclear Phagocytes

Abstract: HIV-1 vpr encodes a 96-amino acid, nuclear protein whose function is not well understood. Unlike the other lentivirus regulatory proteins, Vpr is present in virions at relatively high copy number. In cells, Vpr is localized to the nucleus. Possible functions for vpr consistent with these findings include the nuclear import of preintegration complexes, transactivation of cellular genes, or induction of cellular differentiation. We show here, using both replication competent, macrophage-tropic virus and a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,002
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,207 publications
(1,028 citation statements)
references
References 0 publications
23
1,002
3
Order By: Relevance
“…All cloned viruses were produced from electroporated Jurkat-CCR5 (generous gift from M. Emerman) and normalized by p24 enzyme-linked immunosorbent assay (ELISA) (Perkin-Elmer Life Sciences). We generated a panel of pNL4.3-derived infectious molecular clones in which the envelope gene had been replaced with those encoded by a selection of isolates, including wild-type pNL4.3 (generously contributed by Malcolm Martin through the AIDS Research and Reference Reagent Program) (1), the gp120-deficient virus pNL4.3-E-(generously contributed by Nathaniel Landau through the AIDS Research and Reference Reagent Program) (19,36), pNL-ADA, pNL-JRFL, pNL-YU2, pNL91US005.11, pNL-92MW965.26, pNL-RW020.5, and pNL-92BR020.4 as R5 viruses, pNL-HXB, pNL-92UG021.6, pNL-92UG024.2, and pNL-92HT599.24 as X4 viruses, and finally, pNL-89.6 as R5X4 virus (a generous gift from P. Bieniasz) (97). The primary viruses isolated from matched brain and lymphoid tissues were derived and amplified as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…All cloned viruses were produced from electroporated Jurkat-CCR5 (generous gift from M. Emerman) and normalized by p24 enzyme-linked immunosorbent assay (ELISA) (Perkin-Elmer Life Sciences). We generated a panel of pNL4.3-derived infectious molecular clones in which the envelope gene had been replaced with those encoded by a selection of isolates, including wild-type pNL4.3 (generously contributed by Malcolm Martin through the AIDS Research and Reference Reagent Program) (1), the gp120-deficient virus pNL4.3-E-(generously contributed by Nathaniel Landau through the AIDS Research and Reference Reagent Program) (19,36), pNL-ADA, pNL-JRFL, pNL-YU2, pNL91US005.11, pNL-92MW965.26, pNL-RW020.5, and pNL-92BR020.4 as R5 viruses, pNL-HXB, pNL-92UG021.6, pNL-92UG024.2, and pNL-92HT599.24 as X4 viruses, and finally, pNL-89.6 as R5X4 virus (a generous gift from P. Bieniasz) (97). The primary viruses isolated from matched brain and lymphoid tissues were derived and amplified as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…The Env-deleted luciferase reporter gene containing plasmid (PNL-Luc-E-R ϩ ) was cotransfected into 293 T cells along with the plasmids encoding the MLV Env genes, as previously described. 30 Pseudotyped HIV was prepared as previously described. 31 Fresh monocytes plated in 48-well plates (5 ϫ 10 5 cells per well) were pretreated with morphine (10 Ϫ12 to 10 Ϫ8 mol/L) for 3 hours.…”
Section: Pseudotyped Hiv Infection Assaymentioning
confidence: 99%
“…This suggests that Vpr and MA-NLS are not essential for HIV-1 replication in primary macrophages. Nevertheless, several studies have suggested that Vpr confers an advantage for HIV replication in macrophages (Balliet et al, 1994;Connor et al, 1995). A Vpr-deficient R5 virus efficiently infected T lymphocytes in tonsil cell cultures, but was severely affected in its ability to infect macrophages (Eckstein et al, 2001).…”
Section: Nuclear Importmentioning
confidence: 99%